The Second Vatican Council (1962-1965) and the Regulations on Sacred Art. Past and Influences - Marín Navarro, Víctor (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
Studies on the regulation of contemporary Christian art have focused their attention on a majority in the teaching of Vatican II. However, during the pontificate of Pius XII (1939-1958) is unprecedented in law’s own writings to Eugenio Pacelli, and episcopal documents the work of various characters in the hierarchy as Romano Guardini, Joseph Frings, Giacomo Lercaro or Giovanni Montini himself, among others. Highlighting its crucial role, researchers intend to expand the horizons of artistic rules of Vatican II, stressing the historic significance of these precedents for an overall understanding of the council.